Digital Relationality and Emotional Well-Being: An Integrative Review on Empathy, Ghosting, Narcissism, Loneliness, and Emotional Regulation in Online Interactions (2015–2025) - Santiago-Torner, Carlos; Corral-Marfil, José-Antonio; Tarrats-Pons, Elisenda (Human Behavior and Emerging Technologies, 2026)
This integrative review examines how digitally mediated relational practices shape emotional well-being in contemporary societies, synthesizing research published between 2015 and 2025. Focusing on six interrelated constructs—digital empathy, narcissism, loneliness, ghosting, online friendship dynamics, and emotion regulation—the review draws on a final corpus of 100 peer-reviewed studies indexed in Scopus and Web of Science. The evidence shows that digital platforms are not neutral communication tools but complex sociotechnical environments actively configure how individuals form, sustain, and dissolve emotional bonds. Digitally mediated interactions can foster empathic understanding, emotional support, and relational continuity, yet they also intensify self-presentation pressures, social comparison, and emotional misattunement, particularly among users with narcissistic vulnerabilities. Loneliness emerges not simply from reduced social contact but from discrepancies between relational expectations and the affordances of online communication, especially within digitally mediated friendship networks. Practices such as ghosting constitute a distinct form of relational withdrawal, generating emotional uncertainty, relational disruption, and prolonged ambiguity. Across all themes, emotion regulation plays a central role in shaping how individuals navigate connection, disconnection, and identity in digital contexts. To integrate these findings, the review proposes a three-level model—technological, relational, and normative–cultural—that explains how digital environments recursively shape emotional well-being and friendship dynamics. The article concludes by outlining implications for theory development, digital practices, and future interdisciplinary research.
Keywords: digital communication; emotion regulation; empathy; loneliness; narcissism